Moving toward e-business: customer relationship management alignment in Malaysian small business - Mohamed, Norshidah; Mahmud, Murni; Ahlan, Abdul Rahman; Hussein, Ramlah; Abdul Karim, Nor Shahriza; Aditiawarman, Umar (The Social Sciences Reserach Society, 2013)
The study proposes a research model on customer relationship management (CRM) alignment and investigates the impact of alignment on performance. A total of 300 survey questionnaires were distributed to business owners of small and medium enterprises in Malaysia; 226 were used for analysis. From researchers’ perspective, the research has contributed to new theoretical knowledge on CRM alignment as evident through the development of a new research instrument and research model that explains organizational performance. From practical perspective, the research has clarified the components of CRM alignment and impact of CRM alignment. Implications of research are discussed herein.